Developing Learning Media for the Snakes and Ladders Game Newton's Law with the QuizWhizzer Application to Support Student Learning Motivation - Aulya Dwi Saputri, Reza; Khoirunnisa, Latifa; Nur Diyana, Tsania (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2023)
One important factor that can influence students' learning success is their learning motivation. This research aims to develop the Snakes and Ladders QuizWhizzer Game learning and test the feasibility and influence of using this media on students' learning motivation in the classroom. This research was carried out at Madrasah Tsanawiyah Sleman in November 2023. The method used was research and development (R&D) with the Four D (4D) development model taken from four development stages, namely Define, Design, Develop and Disseminate. The research sample was class VIII students, totaling 5 students. The results of the feasibility test by experts show that the media is suitable for use as a support for learning in the classroom because it can increase students' learning motivation as indicated by the results of the snakes and ladders game and direct interviews. Keywords: Newton's Law, QuizWhizzer, Motivation.